2019
DOI: 10.3389/fnmol.2019.00054
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Peptide Inhibitor Design of Amyloid-β Aggregation

Abstract: Many human neurodegenerative diseases are associated with amyloid fibril formation. Inhibition of amyloid formation is of importance for therapeutics of the related diseases. However, the development of selective potent amyloid inhibitors remains challenging. Here based on the structures of amyloid β (Aβ) fibrils and their amyloid-forming segments, we designed a series of peptide inhibitors using RosettaDesign. We further utilized a chemical scaffold to constrain the designed peptides into β-strand conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…5, E versus C). As expected, the HIV TAR-Tat interface exhibits substantial shape complementarity in its core, as indicated by an S c value of 0.66 -comparable with antibodyantigen interfaces and peptides designed to inhibit ␤-amyloid aggregation (102,133).…”
Section: Molecular Recognition Of Tar By Tat Peptidessupporting
confidence: 64%
“…5, E versus C). As expected, the HIV TAR-Tat interface exhibits substantial shape complementarity in its core, as indicated by an S c value of 0.66 -comparable with antibodyantigen interfaces and peptides designed to inhibit ␤-amyloid aggregation (102,133).…”
Section: Molecular Recognition Of Tar By Tat Peptidessupporting
confidence: 64%
“…Notably, these structures represent snapshots of the kinetic cores of aggregation or end-state morphologies of amyloid fibrils and therefore provide limited information on the underlying aggregation pathways and toxicity-related effects of amyloids. On the other hand, the growing number of highresolution cryo-EM structures has highlighted the in vivo structural diversity of amyloid fibrils 60 , whereas steric zippers have been recently used for the development of targeted therapeutics [61][62][63] . However, determining the structural layout of amyloid fibrils still remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that curcumin derivatives bind strongly to the Aβ peptide. Finally, computational structure-based design was employed for the development of a series of peptide inhibitors for Aβ aggregation [114].…”
Section: Cadd For the Development Of Anti-aβ Aggregation Inhibitorsmentioning
confidence: 99%